2019
DOI: 10.3390/su11082414
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Ride with Others? Meta-Analysis of Factors Influencing Travelers to Carpool

Abstract: Carpooling can be viewed as a simple intervention to reduce congestion, environmental problems, and land use for parking spaces. The present study assembled 18 studies on carpooling from all over the world that were published during the last five years (2014–2018) for a meta-analysis. By calculating effect sizes of 20 different factors, the study aimed to understand user characteristics, motives, and barriers to carpooling, and to gain insights about carpool interventions. Our results indicate that carpooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 47 publications
(79 reference statements)
5
53
1
5
Order By: Relevance
“…He termed this personal agency, and the conceptual dimensions and pathways of agency according to TRC are visualized in Figure 1. or local policy frameworks that prioritize environmental concerns, or high-density cities with established or expanding public transport infrastructure to implement more sustainable travel (see for example [9,10,14,17]). However, what happens in contexts where the relevant values, policies, or infrastructure associated with sustainable travel are absent or have been superseded?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…He termed this personal agency, and the conceptual dimensions and pathways of agency according to TRC are visualized in Figure 1. or local policy frameworks that prioritize environmental concerns, or high-density cities with established or expanding public transport infrastructure to implement more sustainable travel (see for example [9,10,14,17]). However, what happens in contexts where the relevant values, policies, or infrastructure associated with sustainable travel are absent or have been superseded?…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In line with the soft approach, interventions often focus on reinforcing beliefs aligned with sustainable travel via group discussions, role-play, and information campaigns [14][15][16]. In recent years, many innovative projects have capitalized on evolving sustainability values, national or local policy frameworks that prioritize environmental concerns, or high-density cities with established or expanding public transport infrastructure to implement more sustainable travel (see for example [9,10,14,17]). However, what happens in contexts where the relevant values, policies, or infrastructure associated with sustainable travel are absent or have been superseded?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies [3] demonstrate psychological factors such as monetary and time benefits becoming more dominant factors in decisions to use ride-hailing and carpooling services. In relation to rider satisfaction, [4] found surge pricing not to bias Uber towards riders of higher income threshold, but rather, homophilous matching that is, matching riders to drivers of a similar age resulted in higher ratings and further went on to use these insights to predict driver and/or rider retention.…”
Section: Introductionmentioning
confidence: 99%
“…Using a campus travel pattern survey at Ohio State University, Park et al [14] found that safety, flexibility, and parking cost-savings were the most important factors for people willing to be a passenger; while the convenience and opportunities for socializing through a carpool trip were the most influential factors for people willing to take the role of driver. Olsson et al [15] also mentioned that psychological factors, namely monetary and time benefits, reducing congestion, and environmental concerns are more important than socio-demographic variables. In a case study in Lisbon, Correia and Viegas [9] concluded that the passengers joining in carpooling were mostly concerned with travel budgets, namely saving fuel costs, toll costs, and workplace parking costs.…”
Section: Introductionmentioning
confidence: 99%